Deconstruction and Reconstruction of Native Customary Land Tenure in Sarawak - Dimbab, Ngidang (Center for Southeast Asian Studies, 2005)
Contrary to commonly accepted principles of civil society and the ideology of self-determination and governance, the socio-cultural and psychological spaces, territory, boundaries, sovereignty, and customary rights to land resources of the indigenous peoples in Sarawak were not selfdetermined, but were defined during the course of the last century and a half by the Brooke and colonial administrations and by subsequent postcolonial governments. The first two regimes established their dominion and control over the indigenous peoples in Sarawak through autocratic rule and paternalism. In the pretext of protecting native rights to land resources, expatriate administrators deconstructed these rights, which do not owe their existence to statute, and reframed them on the basis of the land laws of their motherland. When customary rights were subjected to formal land codification under the Torrens land registration system, this codification impinged upon the natives’ land inheritance system, their livelihood, their cultural identity, human dignity, and right to exist as discrete groups. Compounding effects of this land codification, the coming into existence of legal pluralism, as well as the exercise of administrative convenience in addressing sensitive land issues have become major sources of land conflict between the Dayak community and private developers and loggers in present-day, post-independence Sarawak.